The effectiveness of branding at Telekom Malaysia Berhad (TM) / Nik Mohd Hanis Zakaria - Zakaria, Nik Mohd Hanis (Faculty of Business and Management, 2009)
The research study is carried out to analyze and identify the factors that influence the effectiveness of branding at Telekom Malaysia Berhad (TM). Actually, the factors that exactly influence brand effectiveness is analyzed and examined by using four major independent variables; promotion, price, service quality and product. It is crucial to analyze and well understand the accurate factors that influence brand effectiveness so that TM brand can last in customers mind and always be a brand of customer’s choice. Therefore, in gaining the customers responses and views, researcher has distributed 80 questionnaires to 80 respondents that are limited to the TM customers in the area of Pasir Puteh Kelantan only. Based on the result, from the examining and analysis of data, there is moderate relationship between promotion, price, product, service quality and brand effectiveness. Hence, it is well-approved that promotion, price, product and service quality are the factors that influence brand effectiveness for Telekom Malaysia (TM) brand.